Odpowiedzi

2009-05-25T21:32:50+02:00
4x=1-3y
x=¼-¾y
5*(¼-¾y)+8y=14
1¼-3¼y+8y=14
8y-3¼y=14-1¼
4¼y=12¾ /4¼
y=3
x=¼-¾*3
x=-2
4x+3y=1
4*(-2)+3*3=1
2009-05-25T21:43:51+02:00
1)Metoda podstawiania:
4x+3y=1 /-3y
5x+8y=14

4x=1-3y //4
5x+8y=14

x=0,25-0,75y
5x+8y=14

x=0,25-0,75y
5(0,25-0,75y)+8y=14

x=0,25-0,75y
1,25-3,75y+8y=14y /-1,25

x=0,25-0,75y
4,25y=12,75 //4,25

x=0,25-0,75y
y=3

x=0.25-0,75*3
y=3

x=-2
y=3

2) Met. prz. współczynników:
4x+3y=1 /*(-5)
5x+8y=14 /*4

-20x-15y=-5
20x+32y=56

17y=51 //17
y=3

4x+3y=1 /*(-8)
5x+8y=14 /*3

-32x-24y=-8
15x+24y=42

-17x=34 //(-17)
x=-2

x=-2
y=3